PENGARUH KEPEMIMPINAN, MOTIVASI DAN KOMITMEN KERJA ORGANISASI TERHADAP KINERJA STAF ADMINISTRASI DI UNIVERSITAS BOSOWA - Hasanuddin, Ahmad Anzhari (Jurnal Ilmiah Ecosystem, 2019)
The purpose of this research is to evaluate and to test the influences of leadership role, motivation and commitment in the organization toward job’s satisfaction and also increasing of the employee’s performance. who find the influence of leadership role, motivation and commitment organization in the workplace toward job’s satisfaction in the job satisfaction.Condition of riset about efect leadership role and motvatione. By using those variables in the evaluation, ones would be expected to solve the problems which happen in Bosowa University the Central Borneo that there are high absences in it, and creating a lower commitment in the organization consequently, loosing of motivation and thus, resulting in lower employee’s performance.The responder in this research were employee’s of organitation for Unibos. The combinations of leadership, motivation and Structural Equation Modeling software are being used to analyzed the collected data. The analyses are proven that leadership role, motivation and commitment in the organization will bring a positive impact and increasing the job’s satisfaction significantly. Furthermore, the job’s satisfaction leadership role and commitment organization will bring a positive effect and increasing the employee’s performance respectfully.This empirical result indicated in order to fulfill and to increase the job’s leadership the organization needs to put an attention in motivation and organization’s commitment values, because these values are verified to influence the highs and lows of job’s satisfaction and. As well as, the job’s satisfaction, leadership role and commitment organization will affect the highs and lows of job’s performance.